Perceptions in Turkey about the war in Ukraine: Implications for the future of EU-Turkey relations - Sinem Adar (Stiftung Wissenschaft und Politik (SWP), 2022)
Undermining the foundational pillars of the post-Cold War security order, Vladimir Putin's war against Ukraine is a watershed event for Europe and the wider world, Turkey included. While Ankara is trying to protect its economy and security interests, anti-Western narratives dominate the public debate. The war has indeed accentuated anti-Westernism as one of the main fault lines of political competition. Given the geopolitical imperatives that February 24 brought to the fore, it is highly likely that, in the short-term, Turkey's NATO membership and its Association Agreement with the EU will - geopolitically and economically - continue to anchor it to the West. Whether or not a full strategic alignment with the EU will accompany such an anchoring is far from certain, however, mainly due to Turkey's domestic political dynamics, but also due to the unclarity about how far the EU is willing to move beyond a transactional approach.
Keywords: 320